Meningkatkan Integritas Pemilu: Mengevaluasi Peran dan Tantangan Badan Pengawas Pemilu di Boyolali, Indonesia - Leodita, Ashra; Prastika, Anggun; Puspaningrum, Puspaningrum (Indonesian Journal Publisher, 2024)
In the pursuit of national progress, the election process serves as a crucial foundation, with the Election Supervisory Agency (ESA) playing a pivotal role in ensuring its integrity. This study focuses on the responsibilities of ESA in minimizing electoral violations by implementing a comprehensive oversight system as a preventive measure. The study employs a normative juridical research method, examining secondary data from academic journals and relevant institutions, and is based on legal frameworks, including the prevailing Election Law. Data collection involved analyzing the Form A report on the Election Supervision Results Number 011/LHP/PM.01.02/SELO/01/2024. The study reveals that despite ESA's efforts, challenges persist, particularly concerning technical regulations from the central sector and the absence of a strategic approach to counter transactional politics. Furthermore, previous elections have highlighted issues related to human resource quality and institutional effectiveness, necessitating significant improvements. The findings indicate a need for enhanced knowledge and supervision during elections, as well as increased technical competence among citizens. These issues contribute to low civic participation in Indonesia. In conclusion, while ESA's role is critical in safeguarding the electoral process, substantial reforms are required to address deficiencies in human resources and the institutional framework, ultimately fostering a more participatory and transparent election system. Future research should focus on developing strategies to enhance ESA's capacity, exploring the role of technology in improving election oversight, and investigating the impact of civic education on voter participation. These areas are crucial for advancing the effectiveness of electoral supervision and promoting democratic engagement in Indonesia.